Peripheral administration of nanomicelle-encapsulated anti-Aβ oligomer fragment antibody reduces various toxic Aβ species in the brain - Akiko Amano; Nobuo Sanjo; Wataru Araki; Yasutaka Anraku; Makoto Nakakido; Etsuro Matsubara; Takami Tomiyama; Tetsuya Nagata; Kouhei Tsumoto; Kazunori Kataoka; Takanori Yokota (Journal of Nanobiotechnology, 2023)
Abstract Background Although a large amount of evidence has revealed that amyloid β (Aβ), especially Aβ oligomers, protofibrils, and pyroglutamated Aβs, participate primarily in the pathophysiological processes of Alzheimer’s disease, most clinical trials of anti-Aβ antibody therapy have never acquired successful efficacy in human clinical trials, partly because peripheral administration of antibody medications was unable to deliver sufficient amounts of the molecules to the brain. Recently, we developed polymeric nanomicelles capable of passing through the blood–brain barrier that function as chaperones to deliver larger amounts of heavy molecules to the brain. Herein, we aimed to evaluate the efficacy of newly developed antibody 6H4 fragments specific to Aβ oligomers encapsulated in polymeric nanomicelles on the development of Alzheimer’s disease pathology in Alzheimer’s disease model mice at the age of emergence of early Alzheimer’s disease pathology. Results During the 10-week administration of 6H4 antibody fragments in polymeric nanomicelles, a significant reduction in the amounts of various toxic Aβ species, such as Aβ oligomers, toxic Aβ conformers, and pyroglutamated Aβs in the brain was observed. In addition, immunohistochemistry indicated inhibition of diameters of Aβ plaques, Aβ-antibody immunoreactive areas, and also plaque core formation. Behavioral analysis of the mice model revealed that the 6H4 fragments-polymeric nanomicelle group was significantly better at maintaining long-term spatial reference memory in the probe and platform tests of the water maze, thereby indicating inhibition of the pathophysiological process of Alzheimer’s disease. Conclusions The results indicated that the strategy of reducing toxic Aβ species in early dementia owing to Alzheimer’s disease by providing sufficient antibodies in the brain may modify Alzheimer’s disease progression.